2009
DOI: 10.1080/15313220903445306
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment in the Hospitality Industry in the Republic of Cyprus: Theory and Prevention

Abstract: The purpose of this exploratory investigation is to identify the nature of the optimal interpersonal (relational) conditions under which sexual harassment in the hospitality industry is likely to occur, as well as the intrapersonal (psychological and emotional) and occupational ramifications of this phenomenon for both the harasser and the harassed. In addition, it attempts to develop specific strategies for minimizing the incidence of sexual harassment by offering both general awareness seminars and guest lec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 26 publications
1
18
0
1
Order By: Relevance
“…In a sample of New York and New Orleans restaurant workers, Agrusa et al (2002) reported the SH incidence rate of 48.9 per cent. Comparatively, the lowest (8 per cent) of SH incidence rate is recorded among hospitality workers in the sample of Theocharous and Philaretou (2009).…”
Section: Literature Reviewmentioning
confidence: 75%
“…In a sample of New York and New Orleans restaurant workers, Agrusa et al (2002) reported the SH incidence rate of 48.9 per cent. Comparatively, the lowest (8 per cent) of SH incidence rate is recorded among hospitality workers in the sample of Theocharous and Philaretou (2009).…”
Section: Literature Reviewmentioning
confidence: 75%
“…Surveys of issues which some perceive as both sensitive and somewhat controversial, have a tendency toward lower response rates (Keegan & Lucas, 2005). Subsequently, and comparing the overall response rate with previous research studies conducted in Cyprus, a response rate > 30% can be considered satisfactory (see for example, Theocharous & Philaretou, 2009;Zopiatis & Constanti, 2007, 2010. Table 1 exhibits the demographic profile of the respondents according to the variables of gender, age, nationality, current employer, educational background, and level of employment (Table 2).…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…In a study that investigated restaurant employees, Weber et al [ 11 ] argue that it is reasonable to say that sexual harassment is more widespread in the restaurant industry because circumstances that can be regarded as sexual harassment in other industries are often not treated as sexual harassment in the restaurant industry. Theocharous and Philaretou [ 12 ] believe that many cases of sexual harassment remain unreported in the hospitality industry. According to their study, sexual harassment not only causes direct financial threat and loss to the victims, female employees, but also seriously damages their future career, such as delaying promotion and loss of income.…”
Section: Literature Review and Conceptual Modelmentioning
confidence: 99%